2022
DOI: 10.3390/app12136315
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Shade Relationship with Age, Gender, and Skin Color in a Saudi Population: A Cross-Sectional Study

Abstract: Objectives: The aim of this study was to assess the relationship between tooth shade among different groups of patients according to their age, gender, and skin color in a Saudi population. Materials and methods:Participants were divided based on age into Group 1 (10–20 years), Group 2 (21–30 years), Group 3 (31–40 years), and Group 4 (41+ years), and according to gender. Tooth shade was measured by Vita easyshade, Shade scanner, 3D Master shade system. The skin color was determined according to the Firzpatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…A root canal treated, partially decoronated maxillary central incisor typodont was selected for this investigation in order to standardize cavity size and depth in all specimens. The typodont is fabricated from an A2 shade material which is one of the most common shades for human teeth [36]. According to the manufacturer optical properties are similar to natural teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A root canal treated, partially decoronated maxillary central incisor typodont was selected for this investigation in order to standardize cavity size and depth in all specimens. The typodont is fabricated from an A2 shade material which is one of the most common shades for human teeth [36]. According to the manufacturer optical properties are similar to natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…According to the manufacturer optical properties are similar to natural teeth. These teeth serve as a standardized scaffold for such a measurement as natural teeth sizes, shades and refractive indices may vary on a large scale [36,37]. Therefore such level of standardization could not have been carried out using natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…proved that patients under the age group of 41 years or more predominantly had A3 shade, whereas the majority with the age of between 21 and 30 years showed B3 shade. [ 18 ] Similarly, a study proved that the common tooth shade in elderly people was A3.5. [ 19 ] All the above-mentioned results of various studies were found to be consistent with the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%